The effect of iron oxide synergism on the structural and magnetic properties of iron-doped ZnO - Adenilson F. dos Santos; Angela Marta da Silva; Thaís Karine de Lima; Noelio O. Dantas; Marcio A. Correa; Anielle Christine A. Silva (Next Materials)
Doping semiconductors with transition metals is a prominent strategy for modifying their magnetic properties, offering numerous innovative applications. This study explores the synergistic effect of iron oxide on the structural and magnetic properties of iron-doped zinc oxide (ZnO) nanoparticles. By introducing high iron (Fe) ion concentrations, we reveal a remarkable interplay between the nanostructure and magnetism. The presence of iron significantly alters the crystalline structure, morphology, and magnetic characteristics of ZnO. Comprehensive analyses using X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy-dispersive spectroscopy (EDS) reveal that secondary magnetic phases, such as maghemite, form at specific iron concentrations, leading to a transition to a ferromagnetic state. This discovery highlights the synergistic effect of iron oxide, offering more profound insights into magnetic doping in semiconductors. It opens new avenues for applications in spintronic devices and nanoscale magnetic data storage. The findings mark a significant advancement in nanomagnetism, highlighting the potential of Fe-doped ZnO/Fe2O3 nanocomposites as a versatile platform for developing next-generation magnetic devices.